Development of 3D-Printed Collagen Scaffolds with In-Situ Synthesis of Silver Nanoparticles - Municoy, Sofia (2022)
UV-irradiation method has grown as an alternative approach to in situ synthetize silver nanoparticles (AgNPs) for avoiding the use of toxic reducing agents. In this work, an antimicrobial material by in situ synthesizing AgNPs within 3D-printed collagen-based scaffolds (Col-Ag) was developed. By modifying the concentration of AgNO3 (0.05 and 0.1 M) and UV irradiation time (2 h, 4 h, and 6 h), the morphology and size of the in situ prepared AgNPs could be controlled. As a result, star-like silver particles of around 23 ± 4 μm and spherical AgNPs of 220 ± 42 nm were obtained for Ag 0.05 M, while for Ag 0.1 M cubic particles from 0.3 to 1.0 μm and round silver precipitates of 3.0 ± 0.4 μm were formed in the surface of the scaffolds at different UV irradiation times. However, inside the material AgNPs of 10–28 nm were obtained. The DSC thermal analysis showed that a higher concentration of Ag stabilizes the 3D-printed collagen-based scaffolds, while a longer UV irradiation interval produces a decrease in the denaturation temperature of collagen. The enzymatic degradation assay also revealed that the in situ formed AgNPs act as stabilizing and reinforcement agent which also improve the swelling capacity of collagen-based material. Finally, antimicrobial activity of Col-Ag was studied, showing high bactericidal efficiency against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria. These results showed that the UV irradiation method was really attractive to modulate the size and shape of in situ synthesized AgNPs to develop antimicrobial 3D-printed collagen scaffolds with different thermal, swelling and degradation properties.